2022
DOI: 10.1111/opo.12998
|View full text |Cite
|
Sign up to set email alerts
|

An initiative to improve follow‐up of patients with diabetic retinopathy

Abstract: Background This study describes the implementation of an electronic medical record (EMR)‐based initiative aimed at identifying and reducing the number of patients with diabetic retinopathy (DR) lost to follow‐up (LTF). Method Providers were enlisted to review the EMRs and re‐engage patients with DR seen 1 year prior and who had not returned for care within the past 6 months. Binary logistic regression analysis was used to identify demographic, clinical and sociomedical factors associated with being LTF, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Coding variation is a major concern in database analyses 34 . This limitation was addressed by conducting a detailed chart review to enhance the accuracy of the clinical classification of each patient identified for outreach 23–25 . Despite finding a strong association between age and becoming LTFU, none of the other characteristics investigated here predicted which patients were more likely to be reached or accept a return to eye care when contacted.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Coding variation is a major concern in database analyses 34 . This limitation was addressed by conducting a detailed chart review to enhance the accuracy of the clinical classification of each patient identified for outreach 23–25 . Despite finding a strong association between age and becoming LTFU, none of the other characteristics investigated here predicted which patients were more likely to be reached or accept a return to eye care when contacted.…”
Section: Discussionmentioning
confidence: 90%
“…Our outreach programme successfully reduced the LTFU rate by considering patient outcomes. Previous telehealth studies targeting patients with open‐angle glaucoma or diabetic retinopathy achieved higher success rates in returning patients to eye care 22–25 . This may be attributed, in part, to the younger age of patients with those conditions compared to advanced AMD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations